Pengaruh fnvestntent Opportunity Cost (IOS) terhadap Harga Saham dengan Earning Per Share (EPS) sebagai Variabel Pemoderasi - Umi Murtini; Ferik Wijaya (Fakultas Bisnis UKDW, 2009)
When Investors want to hry stock on the stock market, they will aamine the arnount of the stock dividend share. It relates n the iwestment opportunity set QOS).This research employed some techniques in measuring IOS, i.e. Markct Yalue of Assets to BookYalue of Assets (MYABYA), Markct Value of Equity toBook Value of Equity (Ifi/EBW), Finn Yalue to Book Yalue of Property, Plant And EEipnent (WPE), Price Earning Ratio (PER), Capital Expendim.re to Market Yalue of Assets (CAPMIIA) and Capital Expenditure to B ook Yalue of Assets (CAPBVA).By employtng common factor analysis, this research took 67 companies as the sample. Arnong these, 30okwere taken as the companies that had high IOS and 30% as the companies which had low IOS. The research analysis of the whole sample and those which had low IOS, showed that the dividend per share, together with IOS, became a moderating variable, whichinfluenced the stock price. Whereas, the analysis of those from the high IOS *plained that dividend per share wos not a moderatingKeywords: Investnent Opportunity Set QOS), Dividendper Share, Prory IOS